A latent class analysis of cannabis use products in a general population sample of adolescents and their association with paranoia, hallucinations, cognitive disorganisation and grandiosity. (June 2021) - Mackie, Clare J.; Wilson, Jack; Freeman, Tom P.; Craft, Sam; Escamilla De La Torre, Thalia; Lynskey, Michael T.
Highlights: Adolescent cannabis users can be categorised into 3 separate groups. High potency cannabis use increases risk of paranoid thoughts. Heavy use of any type of cannabis increases risk of hallucinations. Expansion and social motives can differentiate users based on type of cannabis. Abstract: Adolescents have access to a wide range of cannabis products with patterns of use becoming increasingly diverse. This study aimed to identify subgroups of adolescents in the general population who use similar types of cannabis and their association with psychotic experiences. Data on cannabis use were obtained from 467 adolescents aged between 16 and 17 years. Latent class analysis (LCA) identified groups of adolescents based on the type of cannabis used in the past 12 months. Univariate analysis explored differences in socio-demographics, substance use and mental health symptoms between groups. Multivariate analysis examined associations between class membership and psychotic experiences controlling for frequency and amount of cannabis. Finally, we explored the association between motives for cannabis and class membership using multi-nominal logistic regression. LCA identified 3 classes of adolescents: (i) herbal only (47.9%); (ii) skunk only (20.8%) and (3) mixed use (31.3%). Relative to non-users, skunk only use was associated with a 2-fold increase in paranoia (OR = 2.45, 95% CI = 1.29–4.63), along with, sleep disturbance and anxiety. Monthly cannabis use and consuming 2 or more joints on one occasion was associated with a 2-fold increase in hallucinations (OR = 2.2; 95% CI = 1.0–4.8 and OR = 1.9; 95% CI = 1.2–3.2), but did not reach the Bonferroni corrected p-value. Expansion and conformity motives differentiated the mixed cannabis class from the herbal only class. The findings suggest that different subgroups of cannabis users exist in adolescence as defined by the type of cannabis consumed and are differentially related to psychotic experiences and motives for use.